Insecticide-resistance mechanism of Plutella xylostella (L.) associated with amino acid substitutions in acetylcholinesterase-1: A molecular docking and molecular dynamics investigation. (December 2018) - Sindhu, Thangaraj; Venkatesan, Thiruvengadam; Prabhu, Dhamodharan; Jeyakanthan, Jeyaraman; Gracy, Gandhi R.; Jalali, Sushil Kumar; Rai, Anil
Graphical abstract: Highlights: Development of 3D functional structure of Px-AChE1 by threading method. Conformational changes of the wild-type and mutant proteins was investigated. A298S and G324A mutations affects the stability of the structure Px-AChE1. Two mutations reduces the number of hydrogen bond interactions and docking scores. Insecticide-resistance mechanism of Px -AChE1 was elucidated in detail. Abstract: Acetylcholinesterase-1 (AChE1) is a vital enzyme involved in neurotransmission and represents an attractive insecticide-target for organophosphates and carbamates in Plutella xylostella (Linneaus), an important pest of cruciferous crops worldwide. However, insecticide-resistance often occurs due to mutations, making many organophosphates and carbamates ineffective. In particular, A298S and G324A mutations in AChE1 significantly lower the binding affinity of insecticides. In the present study, the wild-type and mutant AChE1 structures were constructed and their structural stabilities, residual flexibilities were investigated through molecular dynamics simulations. Subsequently, the structural and energetic changes responsible for the insecticide-resistance in AChE1 were analyzed using molecular docking. The results of molecular dynamics simulation showed that the mutant AChE1 shows little structural deviation than the wild-type, indicate the structural instability. Furthermore, the docking results demonstrated that these mutations break the intermolecular hydrogen bonding interactions and thereby affect the prothiofos as well as all insecticide binding. Hence, the results could provide some insights into the resistance mechanism of AChE1 in insecticides binding and helpful in the development of novel insecticides that are less susceptible to insecticide-resistance.